Principles of Marriage in the Perspective of Law Number 1 of 1974 Concerning Marriage in the Framework of a Compilation of Islamic Law - Ahlunnaja, Ahmad; Busriyanti, Busriyanti; Faisol, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Islam is the most complex religion among other religions in all lines of human life, all are regulated in Islam both human relations with God (Hablu minallah) to human relations with humans (Hablu minannas). In the realm of human relations with humans (Hablu minannas), 0basically humans are social creatures, of course, in socializing humans are required to be able to approach emotionally. In Islam, there is an order to carry out obligatory worship that is highly recommended for Muslims, it is called marriage, the meaning of marriage according to Islamic law is marriage, which is a very strong contract or mitsaqan ghalidzan to obey Allah's commands and carry it out in the form of worship, the purpose of marriage in Islam aims to create a household life that is sakinah, mawaddah, and rahmah. Marriage, of course, has a principle, the conditions for carrying out a marriage are five contents of the principles of marriage, the first is the principle of freedom to choose a partner, the second is the principle of equality, the third is mu'asyarah bil ma'ruf, the fourth is the principle of deliberation, the fifth is the principle of mutual acceptance of the five contents of this principle, making it a basic principle in carrying out a marriage. Indonesia is a state of law, all things have rules governing humans that are coercive and remember as well as a marriage that has sacred value, all of which are regulated in law number 1 of 1974 concerning marriage, whose contents in the law include the basics of marriage, the conditions, and pillars of marriage, all of which are contained in the law taken from the essence of Islamic law concerning marriage and all of which are in a collection called the Compilation of Islamic Law.